O trabalho com projetos no Ensino Médio: possibilidades formativas - Paes, Lisandra (2018)
This research aims to report the experiences of teachers involved in the realization of projects integrated into a high school and, from them, identify the teaching view on work with integrated projects, detect the difficulties in its development and to point out ways of contributing to the pedagogical coordinator and the continuing training that can minimize the obstacles pointed out, as well as assist in the development of projects. The moment of writing of this research is singular, as it occurs during the national discussions on changes in high school, also occurring during the training meetings developed in the Municipal Secretary of Education of Sao Paulo with the eight schools of the network that offer this stage of teaching, bringing to the fore the necessity of transformations, presented as viable from the reflective formation of the teaching staff and the theoretical foundation of the pedagogical coordinators. Structured in two major theoretical axes, which interconnect and complement each other, this research brings the writings of Imbernón (2000), Nóvoa (1997), Tardif (2003), Alarcão (2010), Canary (2006) and Garcia (1997), among others, as the basis of the first axis, the teaching training from the perspective of a reflective professional, knowledge producer, from the action of the pedagogical coordinator, cited in authors such as Placco, Almeida and Souza (2015), André (2016), Pessoa e Roldão (2015), which discuss the formation based on collaborative and participatory moments, exchange of experiences, transformers of pedagogical practice. The second axis addressed in this work is the development of integrated projects, under the light, mainly, of Japiassu (1976), Martins (2005 and 2013) and Hernández (1998 and 2007), whose texts they explain the need for educational proposals that transcend borders and find a link between the different areas of knowledge, and present the work with integrated projects as one of the ways to meet this need. The qualitative analysis of responses to the questionnaires applied to teachers is used, and concludes that the greatest difficulties in the development of projects can be carried out through continuing training, provided that this is a space of exchanges and privileges the experiential learning of teachers, in a collaborative way, articulated by the coordinator pedagogical dialogic and cooperatively. The formative possibilities for the development of integrated projects therefore go using strategies such as dual conceptualization or thematic research, that privilege the dialogue and sharing experiences